An analysis of errors in Chinese–Spanish sight translation by Chinese university students—a corpus study - Liu, Shiyang (Frontiers in Psychology, 2025)
Understanding the challenges inherent in Chinese–Spanish sight translation for undergraduate students is essential for enhancing their interpretation ability and accuracy. However, sight translation errors have rarely been studied, especially for Chinese–Spanish language pair. This study builds a corpus of Chinese university students’ Chinese–Spanish sight translation errors, which consists of 294 audio assignments and 2,923 error instances. The corpus of this study has three parameters: error levels, namely, the lexical, syntactic and grammatical; error manifestations that include substitution, addition, and omission; and source text analysis units, which are interpreting topics and sentences. Based on a combination of theories including the error analysis, Contrastive Analysis Hypothesis, the schema theory and Gile’s Effort Model, error analysis was conducted on the corpus to identify prevalent error types, analyze error distribution patterns, and determine error causes. This study employed a combination of quantitative and qualitative analysis. Frequency analysis, chi-square test and error rate were calculated to determine the prevalent error types and error distribution patterns. A qualitative analysis was also realized to determine the causes of errors. Results indicate that substitution was the most frequent error manifestation, whereas addition and omission were much less frequent. Regarding error levels, at the lexical level, sentences with difficult lexical expressions, like four-character words, abstract words, and poetic phrases, tend to concentrate more errors. Substitution of word selection and terminology, and omission of words were prevalent. At the syntactic level, sentence structure and omission of syntactic elements occurred most frequently, particularly in sentences with considerable length or complex structures. At the grammatical level, errors predominantly occur in areas where Chinese and Spanish have strong linguistic differences, such as agreement in gender and number, verb tense and conjugation, prepositions, and articles. The error causes constitute a complex mechanism that includes linguistic differences, negative translation of mother tongue, lack of domain knowledge and cultural understanding, cognitive load, and other factors. This study offers insights into error patterns and their causes in Chinese–Spanish sight translation, and provides a foundation for future studies on various areas in interpreting error analysis and interpreter training.